Between drawing, painting and seeing - Rocha, Angela (Revista ARA, 2022)
The paintings presented here were made up to 2019, most of them having participated in a solo exhibition held in the same year with the title “Notes on painting”, human practice, seen and reviewed and still frequented by the gaze of those who see it. And in particular by Walter Benjamin's look when writing a text that reveals the peculiarities of his look at the images produced by painting and drawing, trying to translate them into words.